Specificity social and political talk shows in Russia - PodobedovaDaria Alekseevna (Communications. Media. Design, 2021)
Social and political talk shows have become part of the practice of Russian television, occupying a separate thematic niche in it. Due to the influence of social and political factors, talk shows of a socio-political nature demonstrate a stable growth in the share of television viewing: in the period from 2017 it has grown from 2 to 7 %. The article examines the emergence of social and political talk shows and analyzes the phenomenon of their popularity. The further development of the talk show format on socio-political topics is predicted.